2014
DOI: 10.3400/avd.oa.13-00073
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Endovascular Abdominal Aortic Aneurysm Repair Outside of the Instructions for Use and Morphological Changes at 3 Years after the Procedure

Abstract: Introduction:We retrospectively analyzed outcomes of patients who had undergone endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA) more than 3 years previously in a single institution. We compared outcomes between patients who underwent EVAR within and outside of the devices' instructions for use (IFU) and examined mid-term morphological changes in AAA. Methods: A total of 275 patients who underwent EVAR for AAA were selected. IFU parameters included aneurysmal neck length, angulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Hoshina et al [4] used a Palmaz stent to prevent type 1a endoleaks in some patients, with excellent midterm results. However, in their study comparing the on-and off-label use of eVar endografts, the displacement of the Palmaz stent occurred in most patients treated with the device, presumably because of the gradual neck dilatation caused by unfolding of the graft [5]. We agree with their conclusion that an aortic cuff, instead of a Palmaz stent, should be used to treat intraoperative type 1a endoleaks.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Hoshina et al [4] used a Palmaz stent to prevent type 1a endoleaks in some patients, with excellent midterm results. However, in their study comparing the on-and off-label use of eVar endografts, the displacement of the Palmaz stent occurred in most patients treated with the device, presumably because of the gradual neck dilatation caused by unfolding of the graft [5]. We agree with their conclusion that an aortic cuff, instead of a Palmaz stent, should be used to treat intraoperative type 1a endoleaks.…”
Section: Discussionsupporting
confidence: 53%
“…Hoshina et al [5] also compared the outcomes in patients who underwent eVar in which the endograft was used on-label (n = 193) with those in patients in whom it was used off-label (n = 82). like us, they usually inserted a Zenith device in patients with a short aortic neck and an excluder endograft in patients with tortuous vessels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown in large clinical cohorts that up to 42% of EVARs are performed outside the instructions for use for commercially available stent grafts. 3,[17][18][19] Multiple measures have been developed to include more of these difficult necks for endovascular treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Data from the EUROSTAR Registry more than a decade ago looking at aneurysm morphology and procedural details of 2272 patients showed that perioperative New knowledge added by this study • Palmaz stenting is effective and safe as a salvage treatment of proximal endoleak during endovascular aortic repair (EVAR).…”
Section: Introductionmentioning
confidence: 99%